Problems and Crisis of Islamic Education Today and in The Future - Hisbullah Nurdin (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2020)
Islamic strategies and tactics must be more effective and efficient, meaning pedagogical, sociological, and cultural. Therefore, the Islamic breath in the person of a Muslim is essential to be able to move the behavior reinforced with extensive knowledge so that he can provide appropriate and useful answers to the challenges of the development of science and technology, and in Islamic education will not be separated from Islamic principles sourced from the basic principles of the Koran. Planning for future education must include three main characteristics of a society, namely: the future of socio, the future of techno, and the future of bio. Besides, Islamic education strategies in facing future challenges include: (1) Building an actual Islamic Education paradigm; (2) Carry out Affective Education; and (3) Improving the quality of teaching staff.